A dubious resurrection of Ochetophila Poepp. ex Endl. (Rhamnaceae) - Tortosa, Roberto Daniel (2008)
The split off of Discaria nana and D. trinervis from the genus Discaria, recently made by KELLERMANN et al. (2005), is not accepted. The occurrence of specimens with morphological intermediacy between both species and D. chacaye, show that those species, that had been segregated into the genus Ochetophila, are closely related to the last species. Moreover, the entire margin of leaves and the petals well developed, considered synapomorphies of Ochetophila, are present in other species of Discaria. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.